Positive electrode material and preparation method and application thereof
By coating solid solution dielectric compounds and phosphates on the surface of lithium-rich manganese-based materials to form a composite cladding layer, the problem of low interface stability of lithium-rich manganese-based materials under high temperature conditions is solved, and the high temperature stability and cycling performance of the battery are significantly improved.
Patent Information
- Application Number
- CN202411941076.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
The interface stability of lithium-rich manganese-based materials is low under high temperature conditions, resulting in a degradation of battery high-temperature cycling performance and even capacity diving.
By coating the solid solution dielectric compound and phosphate on the surface of the lithium-rich manganese-based material, a composite coating layer is formed to inhibit physical contact with the electrolyte and electrochemical side reactions.
The interface stability of the positive electrode material is significantly improved, the decomposition failure of the electrolyte and the dissolution and migration of transition metal ions at the interface of the positive electrode material are inhibited, and the high temperature stability of the battery is significantly improved.
Smart Images

Figure CN119742347A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology and relates to a positive electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are currently the main energy storage device, widely used in electric vehicles and energy storage power stations and other equipment and facilities. The positive electrode material of lithium-ion batteries largely determines the performance of lithium-ion batteries. Excellent positive electrode materials need to meet many requirements, among which the most important are high safety, low cost and high energy density.
[0003] At present, the cathode materials of mainstream electric vehicle power lithium-ion batteries are divided into lithium iron phosphate and ternary cathodes, but neither of them can simultaneously meet the three aspects of high safety, low cost and high energy density. The safety performance of the ternary cathode needs to be further improved, and the cost needs to be continuously reduced; while the energy density of the lithium iron phosphate cathode needs to be further improved. As a result, high-capacity layered lithium-rich cathodes have become a strong competitor for the next generation of cathode materials, which can meet the above three requirements at the same time. However, due to the high operating voltage of lithium-rich cathodes (≥4.5V vs Li / Li + ), its interfacial stability with the electrolyte under high temperature conditions needs to be improved.
[0004] Based on the above research, there is a need to provide a positive electrode material that can meet the three performance aspects of high safety, low cost and high energy density, and has high interface stability with the electrolyte under high temperature conditions. Summary of the invention
[0005] The purpose of the present application is to provide a positive electrode material and a preparation method and application thereof. The positive electrode material suppresses the physical contact and electrochemical side reactions between the positive electrode interface and the electrolyte through interface coating, so that the battery has excellent high-temperature stability, and effectively solves the problem of low interface stability of lithium-rich manganese-based materials under high temperature conditions.
[0006] In order to achieve the purpose of this application, this application adopts the following technical solutions:
[0007] In a first aspect, the present application provides a positive electrode material, the positive electrode material comprising a core and a coating layer on the surface of the core, the core comprising a lithium-rich manganese-based material, and the coating layer comprising a solid solution dielectric compound and a phosphate;
[0008] The chemical formula of the solid solution dielectric compound is Ba α M β TiO3, wherein α+β=1.0, 0<β≤0.3, and M includes a metal element.
[0009] Preferably, the coating layer further comprises a metal oxide.
[0010] Preferably, the metal oxide comprises Al2O3 and / or Y2O3.
[0011] Preferably, the metal element includes La and / or Sr.
[0012] Preferably, the phosphate comprises Li3PO4 and / or Na3PO4.
[0013] Preferably, in the positive electrode material, the mass of the solid solution dielectric compound accounts for 0.2-2.0 wt % of the mass of the inner core.
[0014] Preferably, in the positive electrode material, the mass of the phosphate accounts for 0.5-2.0 wt % of the mass of the core.
[0015] Preferably, in the positive electrode material, the mass of the metal oxide accounts for 0.5-2.0 wt % of the mass of the core.
[0016] Preferably, the chemical formula of the lithium-rich manganese-based material is Li 1+y Ni t Mn u M' 1-y-t-u O 2-a N a , wherein 0.1≤y≤0.2, 0.2≤t≤0.45, 0.5≤u≤0.7, 0.002≤a≤0.02, 0.95≤y+t+u<1.0, M' comprises any one of Mg, Cr, Nb, Ta or W or a combination of at least two thereof, and N comprises F and / or S;
[0017] Preferably, the particle size D50 of the positive electrode material is 3.0-12.0 μm.
[0018] In a second aspect, the present application provides a method for preparing the positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0019] Mixing and sintering a lithium-rich manganese-based material, a solid solution dielectric compound and a phosphate to obtain the positive electrode material;
[0020] The chemical formula of the solid solution dielectric compound is Ba α M β TiO3, wherein α+β=1.0, 0<β≤0.3, and M includes a metal element.
[0021] Preferably, metal oxide is also added during the mixing.
[0022] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode material as described in the first aspect, or comprises the positive electrode material prepared by the preparation method as described in the second aspect.
[0023] Compared with the prior art, this application has the following beneficial effects:
[0024] The present application, by coating a solid solution dielectric compound and a phosphate on the surface of a lithium-rich manganese-based material, can effectively inhibit the side reaction at the interface between the positive electrode and the electrolyte under high temperature conditions, reduce the surface oxidizability of the lithium-rich manganese-based material, effectively improve the interface stability of the positive electrode material, and inhibit the decomposition and failure of the electrolyte, and can also effectively inhibit the dissolution and migration of transition metal ions at the interface of the positive electrode material, block the direct contact between the electrolyte and the positive electrode material or the core, slow down acid corrosion and O release, etc., and significantly improve the high temperature stability of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic diagram of the structure of the positive electrode material described in Example 1 of the present application;
[0026] Figure 2 This is a SEM image of the kernel described in Example 1 of the present application;
[0027] Figure 3 This is a SEM image of the positive electrode material described in Example 1 of the present application;
[0028] Among them, 101 is the inner core, 102 is the coating layer, and 103 is the metal oxide. DETAILED DESCRIPTION
[0029] Due to the high voltage window (≥4.5V vs graphite), the high-capacity layered lithium-rich cathode has a prominent problem of interface stability at high temperatures, which is mainly manifested in that its high-temperature cycle performance is significantly reduced compared with the normal temperature cycle, and in severe cases, even capacity diving occurs. To solve this problem, the existing technology currently uses the idea of coating ternary cathode materials, that is, coating with inert oxides and forming in-situ fast ion conductors, but this type of method cannot solve the problem of interface side reactions of lithium-rich cathodes very well.
[0030] Due to the strong oxidizing properties of the high-valent nickel and manganese metal elements on the surface of lithium-rich manganese-based materials under high temperature and high voltage conditions, it is inevitable that the positive electrode electrolyte will be slowly oxidized and decomposed during long-term use. The oxidative decomposition of the electrolyte is accompanied by a decrease in the valence of the transition metal on the surface of the positive electrode material, which will manifest as a decrease in the average discharge voltage of the battery system where the lithium-rich positive electrode is located, as well as the release of lattice oxygen. The release of lattice oxygen will form oxygen-containing functional groups with the oxidatively decomposed electrolyte organic groups, which will be free in the electrolyte and continue to consume active lithium ions, resulting in active lithium loss. The loss of active lithium will manifest as a continuous decrease in the capacity of the battery system, and in severe cases, even a capacity drop and battery failure. Therefore, it is difficult to significantly improve the high-temperature stability of lithium-rich manganese-based materials by simple oxide coating alone.
[0031] The ideal coating layer for lithium-rich manganese-based materials has a certain dielectric constant to form a surface reverse electric field, and has low resistance at room temperature. As the temperature rises, especially when the temperature reaches 40°C and above, its resistivity increases significantly, which can block interfacial side reactions to a certain extent to protect the various components of the battery and ensure the stability of the system. Therefore, in order to solve the problem of high-temperature stability of lithium-rich manganese-based materials, the present application provides a composite coated positive electrode material, wherein the coating layer of the positive electrode material includes a resistance adaptively regulating solid solution dielectric compound with a positive temperature coefficient characteristic and a phosphate-based fast ion conductor, and the coating layer can achieve the effect of the above-mentioned ideal coating layer, so that the battery system can maintain excellent stability under high voltage and high temperature conditions.
[0032] The technical solution of the present application is further described below through specific implementation methods. Those skilled in the art should understand that the embodiments are only to help understand the present application and should not be regarded as specific limitations of the present application.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0034] In a first specific embodiment, the present application provides a positive electrode material, the positive electrode material comprising a core and a coating layer on the surface of the core, the core comprising a lithium-rich manganese-based material, and the coating layer comprising a solid solution dielectric compound and a phosphate;
[0035] The chemical formula of the solid solution dielectric compound is Ba α M β TiO3, wherein α+β=1.0, 0<β≤0.3, and M includes a metal element.
[0036] The solid solution dielectric compound specified in the present application has a resistance with a positive temperature coefficient, and the resistance can be adaptively adjusted, so that the resistance of the coating layer increases with the increase of the temperature of the battery system in which the positive electrode material is located, thereby effectively inhibiting the interfacial electron conduction of the positive electrode material under high temperature conditions. At the same time, with the help of its dielectric properties, a reverse electric field is formed inside the coating layer, reducing the surface oxidizability of the lithium-rich manganese-based material, effectively reducing the oxidation of the electrolyte by the high-valent and strongly oxidizing transition metal ions on the surface of the lithium-rich positive electrode material, improving the interface stability of the positive electrode material, and inhibiting the decomposition failure of the electrolyte.
[0037] Therefore, the solid solution dielectric compound described in the present application has an exponentially growing resistance at high temperature, can effectively inhibit the side reactions at the interface between the positive electrode and the electrolyte, effectively block the electronic conduction required for the side reactions, and maintain the system at an extremely high health, thereby improving the high temperature cycle performance of the battery system; in addition, although the resistance of the solid solution dielectric compound increases at high temperature, the electronic conductivity and ionic conductivity of the lithium-rich manganese-based material are significantly increased under high temperature conditions, therefore, the addition of the solid solution dielectric compound does not lead to a significant increase in the internal resistance of the system.
[0038] The specific chemical formula of the solid solution dielectric compound described in this application is Ba α M β TiO3, wherein α+β=1.0, 0<β≤0.3, for example, it can be 0.01, 0.05, 0.1, 0.15, 0.2, 0.25 or 0.3, M includes metal elements, and the metal elements refer to metal elements other than Ba and Ti, such as any one or a combination of at least two of Sr, Zr, Ca or La; and Ba in the present application α M β TiO3 is a solid solution type formed in one step, and the Curie temperature can be adjusted by adjusting the β coefficient to obtain a positive electrode material with a small resistance at room temperature and significantly increased resistance at high temperature within the battery operating temperature range of 25 to 60°C. This ensures the capacity and kinetic performance of the positive electrode material at room temperature, while significantly improving the high-temperature stability, blocking high-temperature interface side reactions to a certain extent, avoiding overcharging, and improving high-temperature long-cycle stability.
[0039] The coating layer described in the present application also includes phosphate, which, as a fast ion conductor, can effectively inhibit the dissolution and migration of transition metal ions at the interface of the positive electrode material, block the direct contact between the electrolyte and the positive electrode material or the core, and at the same time, phosphate has good lithium ion conductivity, and plays the role of a physical diaphragm of transition metal ions; therefore, the phosphate fast ion conductor can significantly reduce the dissolution of transition metals on the surface of the positive electrode material, improve the integrity of the long cycle process of the positive electrode surface structure, cut off the corrosion of the electrolyte acidity on the interface of the positive electrode material, and slow down the structural reconstruction and attenuation process. In addition, the PO bond energy in the phosphate group is relatively high, and the O anion structure is highly stable, which can stabilize the lattice O at the high voltage full power state, and avoid the release of the positive electrode lattice O due to the nucleophilic characteristics of the organic group in the electrolyte. Therefore, phosphate plays multiple roles such as slowing down acid corrosion, inhibiting metal ion dissolution and O release, thereby further improving the stability of the positive electrode material.
[0040] The phosphate and solid solution dielectric compound in the coating layer described in the present application also play a synergistic role. Under high temperature conditions, the interface side reaction is aggravated compared to normal temperature. At this time, the significantly increased resistance of the solid solution dielectric compound will effectively inhibit the interface side reaction. The ionic conductivity provided by the phosphate enables the material to have good ion migration during the charge and discharge process to alleviate the increase in polarization caused by the high electronic conductivity during the charge and discharge process. In addition, phosphate can improve ionic conductivity, reduce O release and inhibit transition metal dissolution at room temperature, and has excellent stability and power performance at room temperature. The solid solution dielectric compound can provide a good physical barrier effect. Therefore, the combination of the two can provide excellent and balanced high temperature performance.
[0041] Preferably, the coating layer further comprises a metal oxide; the metal oxide illustratively comprises any one or a combination of at least two of Al2O3, Y2O3, ZnO, MgO, TiO2 or ZrO2.
[0042] The metal oxide described in the present application is combined with the solid solution dielectric compound and the phosphate to form a coating layer, so that the coating layer can be better spread and melt-coated on the surface of the positive electrode material, thereby improving the surface coating effect, better protecting the main material, and isolating the high-valent Ni and Mn ions from direct contact with the electrolyte when fully charged.
[0043] Preferably, the metal oxide comprises Al2O3 and / or Y2O3.
[0044] The metal oxide described in the present application is a metal ion oxide with low oxidizability. On the one hand, it can reduce the melting point and melting effect, making the coating layer dense and uniform. On the other hand, the metal oxide with low oxidizability has extremely high chemical stability, and its metal ion has weak electron-accepting ability and good acid corrosion resistance. Therefore, the contact interface between the positive electrode material and the electrolyte has high stability, thereby effectively enhancing the durability of the coating layer. In addition, in the metal ion oxide with low oxidizability, the metal ion valence state is low, the O content in the structure itself is low, there will be no significant structural decomposition and O release, so it can show good inertness.
[0045] Preferably, the metal element includes La and / or Sr.
[0046] The solid solution dielectric compound Ba described in this application α M β M in TiO3 is preferably La and / or Sr, which can effectively reduce the temperature point at which its resistance increases significantly, namely the Curie temperature, so that it maintains a low resistance below this temperature and provides a significantly increased resistance after exceeding this temperature, so as to significantly reduce the interface side reaction under high temperature conditions and improve the high temperature service life of the battery; in addition, La / Sr elements have good electrochemical inertness and can improve the solid solution dielectric compound Ba α M β Durability of TiO3.
[0047] Preferably, the phosphate comprises Li3PO4 and / or Na3PO4.
[0048] The phosphate described in the present application is selected from Li3PO4 and / or Na3PO4, which can provide excellent ionic conductivity and effectively inhibit the dissolution of transition metal ions, thereby improving the stability of the material interface structure, inhibiting gas release, and making the positive electrode material have excellent power performance, thereby extending the service life of the positive electrode material at room temperature.
[0049] Preferably, in the positive electrode material, the mass of the solid solution dielectric compound accounts for 0.2-2.0wt% of the mass of the inner core, for example, it can be 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] The mass of the solid solution dielectric compound described in the present application accounts for the mass of the inner core=the mass of the solid solution dielectric compound / the mass of the inner core.
[0051] Preferably, in the positive electrode material, the mass of the phosphate accounts for 0.5-2.0wt% of the mass of the core, for example, it can be 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Similarly, the mass of the phosphate to the mass of the inner core = the mass of the phosphate / the mass of the inner core.
[0053] Preferably, in the positive electrode material, the mass of the metal oxide accounts for 0.5-2.0wt% of the mass of the inner core, for example, it can be 0.5wt%, 0.6wt%, 0.8wt%, 1wt%, 1.2wt%, 1.4wt%, 1.6wt%, 1.8wt% or 2wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] The addition amount of each component in the coating layer of the present application is reasonably selected, which can further improve the coating effect and promote the role of the components; among them, the use of an appropriate amount of solid solution dielectric compound will not lead to a significant increase in the internal resistance of the system, and the electronic conductivity of the interface between the positive electrode material and the electrolyte can be kept similar to or slightly lower than that at room temperature through reasonable regulation of the coating amount, thereby significantly reducing the degree of side reactions and enabling the battery to achieve a cycle performance close to that under normal temperature conditions at high temperature.
[0055] Similarly, the mass of the metal oxide to the mass of the inner core = the mass of the metal oxide / the mass of the inner core.
[0056] Preferably, the chemical formula of the lithium-rich manganese-based material is Li 1+y Ni t Mn u M' 1-y-t-u O 2-a N a , wherein 0.1≤y≤0.2, for example, it can be 0.1, 0.15 or 0.2, 0.2≤t≤0.45, for example, it can be 0.2, 0.3, 0.4 or 0.45, 0.5≤u≤0.7, for example, it can be 0.5, 0.6 or 0.7, 0.002≤a≤0.02, for example, it can be 0.002, 0.005, 0.01, 0.015 or 0.02, 0.95≤y+t+u<1.0, for example, it can be 0.95, 0.96, 0.97, 0.98 or 0.99, M' includes any one of Mg, Cr, Nb, Ta or W or a combination of at least two of them, and N includes F and / or S.
[0057] The lithium-rich manganese-based material of the core described in the present application also contains a specific content of doping elements, which can further improve the cycle stability of the positive electrode material.
[0058] Preferably, the particle size D50 of the positive electrode material is 3.0-12.0 μm, for example, 3.0 μm, 5.0 μm, 7.0 μm, 9.0 μm, 11.0 μm or 12.0 μm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] The particle size D50 mentioned in the present application refers to the particle size when the volume of material particles reaches 50% when measured from the smallest particle size in the volume-based particle size distribution.
[0060] The particle size D50 of the positive electrode material described in the present application is within an appropriate range, which can ensure its comprehensive properties such as good ion transport properties and good capacity performance.
[0061] In a second specific embodiment, the present application provides a method for preparing the positive electrode material as described in the first specific embodiment, the preparation method comprising the following steps:
[0062] Mixing and sintering a lithium-rich manganese-based material, a solid solution dielectric compound and a phosphate to obtain the positive electrode material;
[0063] The chemical formula of the solid solution dielectric compound is Ba α M β TiO3, wherein α+β=1.0, 0<β≤0.3, and M includes a metal element.
[0064] The positive electrode material described in the present application can be obtained by directly mixing and sintering the core material and the coating layer material, and the preparation method is simple and convenient.
[0065] The solid solution dielectric compound described in the present application is a solid solution type Ba α M β TiO3, rather than the product of low-temperature sintering of a mixture of BaTiO3 and SrTiO3, therefore, the solid solution type Ba α M β The Curie temperature of TiO3 can be adjusted by adjusting the β coefficient to obtain a positive electrode material with a small resistance at room temperature and a significantly increased resistance at high temperature within the battery operating temperature range of 25 to 60°C.
[0066] Exemplarily, the Ba α M β The preparation method of TiO3 comprises the following steps:
[0067] According to the formula, barium carbonate, carbonate of metal M and titanium oxide are mixed and sintered to obtain the Baα M β TiO3.
[0068] As the preparation of Ba α M β The preferred technical solution of TiO3 includes the following steps: using barium carbonate, carbonate of metal M and titanium oxide as raw materials, mixing them according to the stoichiometric ratio, and after fully mixing, air-flow crushing the mixed system to ensure that the average particle size D of the raw materials based on the volume 50 <3.0 μm (for example, 2.9 μm, 2.5 μm, 2.0 μm or 1.5 μm), then the mixed raw materials are dispersed in water, sand-milled, dried, and sieved to obtain the average particle size D based on volume 50 <1.0 μm, and finally sintering the mixed powder at a high temperature of 1300-1500°C (for example, 1300°C, 1300°C, 1400°C or 1500°C) for 4-6 hours (for example, 4 hours, 5 hours or 6 hours), and air-flow crushing and sieving the sintered solid to obtain a solid solution dielectric compound Ba with a particle size of <3 μm. α M β TiO3; The chemical formula of the sintering process can be expressed as:
[0069] BaCO3=BaO+CO2↑
[0070] MCO3=MO+CO2↑
[0071] αBaO+βMO+TiO2=Ba α M β TiO3
[0072] Preferably, the sintering temperature is 750-830°C, for example, 750°C, 800°C or 830°C, and the holding time is 10-15h, for example, 10h, 12h, 14h or 15h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] Preferably, after the sintering, the temperature is naturally lowered to room temperature, and the positive electrode material is obtained after sieving.
[0074] Preferably, metal oxide is also added during the mixing.
[0075] Preferably, the method for preparing the lithium-rich manganese-based material comprises the following steps:
[0076] The precursor material, the lithium salt, the M'-containing compound and the N-containing compound are mixed and calcined, and then naturally cooled to room temperature and sieved to obtain the lithium-rich manganese-based material.
[0077] Preferably, the calcination is carried out in a box furnace or a roller kiln, the calcination temperature is 850-950°C, for example, 850°C, 900°C or 950°C, and the insulation time is 10-15h, for example, 10h, 12h, 14h or 15h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0078] Preferably, the lithium salt comprises lithium carbonate and / or lithium hydroxide.
[0079] Preferably, the M′-containing compound includes any one of Nb 2 O 5 , WO 3 , Ta 2 O 5 , MgO or Cr 2 O 3 , or a combination of at least two thereof.
[0080] Preferably, the N-containing compound comprises LiF and / or Li2S.
[0081] Preferably, the method for preparing the precursor material comprises the following steps:
[0082] In a protective gas, a metal salt solution, a precipitant solution and a complexing agent solution are subjected to a coprecipitation reaction. After the particle size grows to a target size, the feeding is stopped and the slurry is collected. The collected slurry is aged, washed, centrifuged and dried to obtain the precursor material.
[0083] Preferably, the metal salt solution comprises nickel salt and manganese salt.
[0084] In a third specific embodiment, the present application provides a lithium-ion battery, which includes the positive electrode material as described in the first specific embodiment, or includes the positive electrode material prepared by the preparation method as described in the second specific embodiment.
[0085] The lithium-ion battery provided in the present application comprises a positive electrode plate containing the positive electrode material, a negative electrode plate, an electrolyte and a separator, wherein the separator is optional.
[0086] Preferably, the positive electrode plate comprises a positive electrode current collector and an active material layer coated on at least one side of the positive electrode current collector, and the active material layer comprises the positive electrode material, positive electrode binder and positive electrode conductor described in the first specific embodiment.
[0087] Preferably, the positive electrode binder includes any one or a combination of at least two of polyvinylidene fluoride, polytetrafluoroethylene, polyethylene glycol, polyimide, styrene-butadiene rubber, carboxymethyl cellulose, polyacrylic acid, polyacrylonitrile or polyacrylate. Those skilled in the art can select according to needs, and no specific limitation is made here.
[0088] Preferably, the positive electrode conductive agent includes any one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene or carbon nanofibers, or a combination of at least two thereof. Those skilled in the art may select the one according to their needs, and no specific limitation is made here.
[0089] Preferably, the negative electrode plate comprises a negative electrode current collector and a negative electrode active material layer covering the surface of the negative electrode current collector.
[0090] Preferably, the negative electrode active material layer includes a negative electrode binder, a negative electrode active material and a negative electrode conductor.
[0091] Preferably, the negative electrode binder includes any one of polytetrafluoroethylene, sodium carboxymethyl cellulose, styrene-butadiene rubber, polyvinylidene fluoride, nitrile rubber, styrene-ethylene-butylene-styrene copolymer, styrene-butadiene-styrene copolymer, lithium polyacrylate, sodium polyacrylate, sodium alginate or lithium alginate, or a combination of at least two thereof. Those skilled in the art can select the one according to their needs, and no specific limitation is made here.
[0092] Preferably, the negative electrode active material includes any one of graphite, soft carbon, hard carbon, silicon oxygen or silicon carbon, or a combination of at least two thereof. Those skilled in the art may select the material according to their needs, and no specific limitation is made here.
[0093] Preferably, the negative electrode conductive agent includes any one of conductive carbon black, carbon nanotubes, vapor-grown carbon nanotubes or nano-carbon fibers, or a combination of at least two of them. Those skilled in the art can select according to needs, and no specific limitation is made here.
[0094] Preferably, the present application does not specifically limit the type of electrolyte, and any known electrolyte material can be used in the present application without violating the concept of the present application. As an illustrative example, the electrolyte can be a liquid electrolyte, a solid electrolyte, or a mixture of a solid electrolyte and a liquid electrolyte.
[0095] In addition, the electrolyte used in the present application may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten inorganic electrolyte, etc., which can be used in the manufacture of a secondary battery, but is not limited thereto.
[0096] Preferably, the electrolyte can be a solid electrolyte, and the solid electrolyte particles can contain any one or a combination of at least two of one or more polymer components, oxide solid electrolytes, sulfide solid electrolytes, halide solid electrolytes, borate solid electrolytes, nitride solid electrolytes or hydride solid electrolytes. Those skilled in the art can choose according to needs, and no specific limitation is made here.
[0097] Specifically, the electrolyte may include an organic solvent and a lithium salt.
[0098] Preferably, the organic solvent can use an ester solvent, such as methyl acetate, ethyl acetate, γ-butyrolactone and E-caprolactone; an ether solvent, such as dibutyl ether or tetrahydrofuran; a ketone solvent, such as cyclohexanone; an aromatic hydrocarbon solvent, such as benzene and fluorobenzene; a carbonate solvent, such as dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl methyl carbonate, ethylene carbonate and propylene carbonate; an alcohol solvent, such as ethanol and isopropanol; a nitrile, such as R-CN (wherein R is a linear, branched or cyclic C2-C20 hydrocarbon group, and may contain a double bond aromatic ring or an ether bond); an amide, such as dimethylformamide; a dioxolane, such as 1,3-dioxolane; or sulfolane.
[0099] Any compound can be used as the lithium salt without particular limitation, as long as it can provide the lithium ions used in the lithium secondary battery. For example, the lithium salt source includes but is not limited to any one of LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4 or LiCF3SO3, or a combination of at least two thereof.
[0100] The main function of the separator described in the present application is to separate the negative electrode plate from the positive electrode plate and provide a path for the movement of lithium ions; any separator can be used without particular limitation, as long as it is a separator commonly used in secondary batteries. In particular, a separator having excellent electrolyte wettability and low resistance to ion movement in the electrolyte is preferred. Specifically, a porous polymer film can be used, for example, a porous polymer film made of a polyolefin polymer: ethylene homopolymer, propylene homopolymer, ethylene / butene copolymer, ethylene / hexene copolymer and ethylene / methacrylate copolymer, or a laminated structure having two or more layers thereof. In addition, a typical porous non-woven fabric can be used, for example, a non-woven fabric formed of glass fiber, polyethylene terephthalate fiber, etc. having a high melting point. In addition, a coated separator containing a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and can be selectively used in a single-layer or multilayer structure.
[0101] The technical solution of the present application is further illustrated by means of specific embodiments below.
[0102] Example 1
[0103] This embodiment provides a positive electrode material, the structural schematic diagram of the positive electrode material is as follows Figure 1 As shown, it includes a core 101 and a coating layer 102 on the surface of the core 101, and the surface of the coating layer 102 also has a metal oxide 103 that is not completely melted and coated in an island shape;
[0104] The core 101 includes a lithium-rich manganese-based material. The lithium-rich manganese-based material is Li 1.145 Ni 0.295 Mn 0.55 Nb 0.005 Mg 0.005 O 1.995 S 0.005 ;
[0105] The coating layer 102 includes a solid solution dielectric compound, a phosphate and a metal oxide. The solid solution dielectric compound is Ba 0.75 Sr 0.25 TiO3, the phosphate is Li3PO4, and the metal oxide is Al2O3;
[0106] The particle size D50 of the positive electrode material is 10.2 μm; in the positive electrode material, the mass of the solid solution dielectric compound accounts for 1.0 wt% of the mass of the core, the mass of the phosphate accounts for 1 wt% of the mass of the core, and the mass of the metal oxide accounts for 1 wt% of the mass of the core;
[0107] The preparation method of the positive electrode material comprises the following steps:
[0108] (1) preparing a nickel and manganese salt solution with a concentration of 2.5 mol / L as a metal salt solution, wherein the nickel and manganese sources are nickel sulfate and manganese sulfate, respectively, and the molar ratio of nickel ion to manganese ion is 35:65; preparing a 10 mol / L sodium hydroxide solution and a 10 wt% ammonia complexing agent solution;
[0109] (2) Fill a 50L reactor with clean water, set the stirring speed of the reactor to 800 rpm, the temperature to 55°C, and introduce nitrogen gas. After venting for 2 hours, introduce the metal salt solution described in step (1) into the reactor at a flow rate of 2 L / min, introduce the sodium hydroxide solution described in step (1) at a flow rate of 0.5 L / min, and introduce the ammonia complexing agent solution described in step (1) at a flow rate of 0.05 L / min, and maintain the pH of the reaction system at 9.8;
[0110] (3) Wait until the particle size in the system of step (2) grows to D 50 When the particle size is 10.0 μm, the feed is stopped and the slurry in the kettle is collected;
[0111] (4) The slurry collected in step (3) is aged, washed, centrifuged and dried to obtain a precursor material Ni 0.35 Mn 0.65 (OH)2;
[0112] (5) mixing the precursor material of step (4) with lithium carbonate at a metal ion molar ratio of 1:1.34, adding a formula amount of Nb2O5, MgO and Li2S, mixing them thoroughly and evenly, sintering them in a box furnace at a sintering heating rate of 2°C / min and a sintering temperature of 950°C. After keeping the temperature for 12 hours, naturally cooling to room temperature, sieving, and obtaining the lithium-rich manganese-based material;
[0113] (6) According to the formula, the lithium-rich manganese-based material, solid solution dielectric compound, phosphate and metal oxide described in step (5) are fully mixed, and sintered in a box furnace at a heating rate of 2° C. / min and a sintering temperature of 780° C. After keeping warm for 10 hours, the mixture is naturally cooled to room temperature and sieved to obtain the positive electrode material;
[0114] Wherein, the solid solution dielectric compound Ba 0.75 Sr 0.25 The preparation method of TiO3 comprises the following steps: using barium carbonate, strontium carbonate and titanium oxide as raw materials, mixing them according to a stoichiometric ratio, and then air-grinding the mixed system to obtain a particle size D 50 The mixed raw material is dispersed in water, sand-milled, dried, and sieved to obtain a particle size D 50 The mixed powder was sintered at a high temperature of 1400°C for 5 hours, and the sintered solid was air flow crushed and sieved to obtain D 50 A solid solution dielectric compound of 1 μm;
[0115] The SEM image of the core of this embodiment is as follows: Figure 2 As shown, the grain boundaries are clear, the surface is smooth and has no attachments. The SEM image of the positive electrode material is as follows Figure 3 As shown, part of the grain boundaries on the surface of the positive electrode material are covered by a molten coating layer, the number and size of the gaps between the primary particles are significantly reduced, and at the same time, there are some island-shaped metal oxides on the surface that have not been completely melted due to their high thermal stability.
[0116] Example 2-Example 30 provides a positive electrode material, which differs from Example 1 in the selection of the inner core, solid solution dielectric compound, phosphate and metal oxide, the mass ratio of the solid solution dielectric compound, phosphate and metal oxide to the inner core, and the particle size D50 of the positive electrode material. The rest is the same as Example 1.
[0117] Comparative Examples 1 to 10 provide a positive electrode material, which differs from Example 1 in the selection of the core, the solid solution dielectric compound, the phosphate and the metal oxide, the mass ratio of the solid solution dielectric compound, the phosphate and the metal oxide to the core, and the particle size D50 of the positive electrode material. The rest is the same as Example 1. In Comparative Example 9, Ba 0.75 Sr 0.25 TiO3 is replaced by 0.75BaTiO3·0.25SrTiO3. The preparation method of 0.75BaTiO3·0.25SrTiO3 includes: mixing BaTiO3 and SrTiO3 in a molar ratio of 0.75:0.25 and sintering at 1400°C for 5 hours, followed by air flow crushing and screening.
[0118] The compositions of the inner core, solid solution dielectric compound, phosphate and metal oxide of the above embodiments and comparative examples, the mass ratio of the solid solution dielectric compound, phosphate and metal oxide to the inner core, and the particle size D50 of the positive electrode material are shown in Table 1, wherein the particle size D50 is measured by a laser particle size instrument.
[0119] Table 1
[0120]
[0121]
[0122]
[0123]
[0124] The actual chemical composition of the positive electrode materials obtained in the above examples and comparative examples was determined by ICP-AES, and the test results are shown in Table 2:
[0125] Table 2
[0126]
[0127]
[0128]
[0129] As can be seen from Table 2, the trace element results measured by ICP-AES correspond to the experimental design values as a whole. Each sample has a small test fluctuation or error to varying degrees, and the difference from the theoretical value does not exceed 20%. Therefore, it is proved through experiments that the design of this application is consistent with the actual situation.
[0130] The positive electrode materials described in the above embodiments and comparative examples are assembled into a liquid button half-cell, and the assembly method is: the obtained positive electrode material, Super-P (conductive carbon black) and PVDF (polyvinylidene fluoride) are added to NMP (N-methylpyrrolidone) at a mass ratio of 94:3:3 and mixed evenly to obtain a slurry, and the obtained slurry is sequentially subjected to coating-drying-punching-rolling to obtain a positive electrode sheet, and the button battery stainless steel shell, the positive electrode sheet, the PP diaphragm and the lithium sheet are stacked in sequence, and a certain amount of electrolyte is added and then packaged and kept still to obtain a liquid button half-cell.
[0131] The liquid button half-cell was subjected to the following electrochemical performance tests:
[0132] (1) 0.2C discharge capacity test
[0133] Test method: At 25°C, after the assembled battery has been idle for 5 hours, it is charged to 4.55V at a constant current of 0.2C, then charged to a cut-off current of 0.05C at a constant voltage of 4.55V, and then discharged to 2.5V at a constant current of 0.2C after being idle for 5 minutes. The resulting discharge capacity is the 0.2C discharge capacity.
[0134] (2) First Coulombic efficiency
[0135] Test method: At 25°C, after the assembled battery has been idle for 5 hours, it is charged to 4.55V at a constant current of 0.2C, then charged to a cut-off current of 0.05C at a constant voltage of 4.55V, and then discharged to 2.5V at a constant current of 0.2C after being idle for 5 minutes; the obtained discharge capacity / charge capacity is the first coulombic efficiency.
[0136] (3) Capacity retention rate after 300 cycles at 1.0C high temperature
[0137] Test method: After testing the first discharge capacity of the battery at 25°C, transfer the battery to a 45°C constant temperature incubator and charge it to 4.55V at a constant current of 1.0C, then charge it at a constant voltage of 4.55V until the cut-off current is equal to 0.05C. After standing for 5 minutes, discharge it to 2.5V at a constant current of 1.0C; repeat this 300 times, i.e., charge and discharge it for 300 cycles at a charge and discharge rate of 1.0C / 1.0C. The discharge capacity of the 300th cycle / the discharge capacity of the 1st cycle is the capacity retention rate of 1.0C / 1.0C cycles for 300 cycles.
[0138] The electrochemical performance test results are shown in Table 3:
[0139] Table 3
[0140]
[0141]
[0142] From Table 3 we can see that:
[0143] (1) It can be seen from Examples 1-30 and Comparative Example 1 that the present application adopts a specific coating layer, which can improve the high-temperature cycle performance of the positive electrode material, and the positive electrode material also has a higher specific capacity; it can be seen from Example 1 and Comparative Examples 2-4 that when only solid solution dielectric compounds, phosphates or metal oxides are used for coating alone, the high-temperature long-cycle stability of the positive electrode material cannot be effectively improved, because a single coating layer can only improve a single aspect of performance under high temperature conditions, but the final high-temperature performance depends on the weak link of the material performance, and needs to be improved synergistically to improve the lower limit of the "short board" to finally obtain a positive electrode material with excellent high-temperature performance, and the composite coating of the present application can play a synergistic role to obtain a positive electrode material with excellent high-temperature performance; it can be seen from Example 1 and Comparative Examples 5-6 that when the coating layer lacks phosphate or solid solution dielectric compounds, the high-temperature performance of the positive electrode material will decrease, and the lack of solid solution dielectric compounds has a more obvious impact on the high-temperature performance.
[0144] (2) It can be seen from Example 1 and Comparative Examples 7-8 that replacing the solid solution dielectric compound of the present application with BaTiO3 or SrTiO3 alone cannot effectively guarantee the room temperature and high temperature performance of the positive electrode material. Since the pure phase BaTiO3 has a low resistance at room temperature, its resistance will increase exponentially at a Curie temperature of about 120°C, and the Curie temperature of pure phase SrTiO3 is close to absolute zero, and it has an extremely high resistivity at room temperature. Therefore, although the BaTiO3 coating component has a high dielectric constant in the battery operating temperature range of 25 to 60°C, its resistance is low at high temperature, and its effect on improving the long-term cycle stability at high temperature is limited. O3 can easily lead to the positive electrode material having a large resistance at room temperature and having difficulty in exerting its capacity; it can be seen from Example 1 and Comparative Example 9 that the solid solution dielectric compound described in the present application is a solid solution type substance, while in Comparative Example 9, the solid solution type substance of the present application is replaced with a non-solid solution substance, and the product of the physical mixing and high-temperature calcination of BaTiO3 and SrTiO3 in Comparative Example 9 is not a solid solution, because the finished perovskite products (BaTiO3 and SrTiO3) have very high structural stability, and it is difficult to fully react and dissolve with each other to obtain a solid solution when sintered at high temperature, so the high-temperature performance of the positive electrode material cannot be effectively improved; it can be seen from Example 1 and Comparative Example 10 that Ba α M β In TiO3, the β value cannot be too large, otherwise it will affect its performance and fail to effectively improve the high-temperature cycle performance of the positive electrode material.
[0145] (3) It can be seen from Examples 1 and 17-21 that the stability of the positive electrode material with co-doped anions and cations in the core is slightly higher than that of the positive electrode material with single anion or single cation doping. The present application preferably dopes anions and cations in the core lithium-rich manganese-based material, and preferably a suitable doping amount to ensure that the doping does not affect the capacity and high-temperature cycle stability; It can be seen from Examples 1 and 22 that the addition of metal oxides in the coating layer of the present application can further enhance the coating effect and exert a synergistic effect, thereby further improving the performance of the positive electrode material; It can be seen from Examples 1 and 23-28 that the solid solution dielectric compound, phosphate and metal oxide preferably have a suitable coating amount, which on the one hand ensures the effective effect of the coating component, and on the other hand ensures the normal migration of ions, thereby further improving the performance of the positive electrode material; It can be seen from Examples 1 and 29 that the Ba in the present application α M β M in TiO3 is preferably La and / or Sr, which can further promote the effect of the solid solution dielectric compound and improve the performance of the positive electrode material. It can be seen from Example 1 and Example 30 that the particle size D50 of the positive electrode material described in the present application is preferably within a suitable range.
[0146] In summary, the present application provides a positive electrode material and a preparation method and application thereof. The positive electrode material suppresses the physical contact and electrochemical side reactions between the positive electrode interface and the electrolyte through interface coating, so that the battery has excellent high-temperature stability, and effectively solves the problem of low interface stability of lithium-rich manganese-based materials under high temperature conditions.
[0147] The above description is only a specific implementation manner of the present application, but the protection scope of the present application is not limited thereto. Technicians in the relevant technical field should understand that any changes or substitutions that can be easily thought of by technicians in the relevant technical field within the technical scope disclosed in the present application are within the protection scope and disclosure scope of the present application.
Claims
1. A positive electrode material, characterized in that: The positive electrode material comprises a core and a coating layer on the surface of the core, wherein the core comprises a lithium-rich manganese-based material, and the coating layer comprises a solid solution dielectric compound and a phosphate; The chemical formula of the solid solution dielectric compound is Ba α M β TiO3, wherein α+β=1.0, 0<β≤0.3, and M includes a metal element.
2. The positive electrode material according to claim 1, characterized in that The coating layer also includes a metal oxide.
3. The positive electrode material according to claim 2, characterized in that The metal oxide includes Al2O3 and / or Y2O3.
4. The positive electrode material according to any one of claims 1 to 3, characterized in that The metal element includes La and / or Sr.
5. The positive electrode material according to any one of claims 1 to 3, characterized in that The phosphate includes Li3PO4 and / or Na3PO4.
6. The positive electrode material according to claim 2, characterized in that In the positive electrode material, the mass of the solid solution dielectric compound accounts for 0.2-2.0wt% of the mass of the core; And / or, in the positive electrode material, the mass of the phosphate accounts for 0.5-2.0wt% of the mass of the core; And / or, in the positive electrode material, the mass of the metal oxide accounts for 0.5-2.0wt% of the mass of the core.
7. The positive electrode material according to any one of claims 1 to 3, characterized in that The general chemical formula of the lithium-rich manganese-based material is Li 1+y Ni t Mn u M' 1-y-t-u O 2-a N a , wherein 0.1≤y≤0.2, 0.2≤t≤0.45, 0.5≤u≤0.7, 0.002≤a≤0.02, 0.95≤y+t+u<1.0, M' comprises any one of Mg, Cr, Nb, Ta or W or a combination of at least two thereof, and N comprises F and / or S; And / or, the particle size D50 of the positive electrode material is 3.0-12.0 μm.
8. A method for preparing the positive electrode material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Mixing and sintering a lithium-rich manganese-based material, a solid solution dielectric compound and a phosphate to obtain the positive electrode material; The chemical formula of the solid solution dielectric compound is Ba α M β TiO3, wherein α+β=1.0, 0<β≤0.3, and M includes a metal element.
9. The preparation method according to claim 8, characterized in that: Metal oxides are also added during the mixing.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode material according to any one of claims 1 to 7, or comprises the positive electrode material prepared by the preparation method according to claim 8 or 9.
Citation Information
Cited By
Positive electrode material, and preparation method therefor and use thereof
WO2026138988A1